Racial profiling for induction of labour: improving safety or perpetuating racism?. (2nd November 2021) - Douglass, Christine; Lokugamage, Amali
Abstract : This article was published on BMJ Opinion on 15 October 2021 (https://blogs.bmj.com/bmj/2021/10/15/racial-profiling-for-induction-of-labour-improving-safety-or-perpetuating-racism/ ).